2013
DOI: 10.1016/j.progsurf.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic electron tunneling process for alkanethiol self-assembled monolayers

Abstract: Recent investigations of inelastic electron tunneling spectroscopy (IETS) for alkanethiol self-assembled monolayers (SAMs) are reviewed. Alkanethiol SAMs are usually prepared by immersing a gold substrate into a solution of alkanethiol molecules, and they are very stable, even under ambient conditions. Thus, alkanethiol SAMs have been used as typical molecules for research into molecular electronics. Infrared spectroscopy and electron energy loss spectroscopy (EELS) have frequently been employed to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 133 publications
1
18
0
Order By: Relevance
“…To measure the conductance (dI/dV) and IET signal (d 2 I/dV 2 ), a modulation voltage (2,338.7 Hz and 1-mV rms amplitude) is added to the sample bias, and the first and second harmonics in the current are detected by a lock-in amplifier (HF2LI; Zurich Instruments). In the text, the IETS signal is normalized to the conductance (6,21), i.e., (d 2 I/dV 2 )/(dI/dV) has been plotted. The complete set of the IETS are shown in SI Appendix, Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the conductance (dI/dV) and IET signal (d 2 I/dV 2 ), a modulation voltage (2,338.7 Hz and 1-mV rms amplitude) is added to the sample bias, and the first and second harmonics in the current are detected by a lock-in amplifier (HF2LI; Zurich Instruments). In the text, the IETS signal is normalized to the conductance (6,21), i.e., (d 2 I/dV 2 )/(dI/dV) has been plotted. The complete set of the IETS are shown in SI Appendix, Figs.…”
Section: Methodsmentioning
confidence: 99%
“…The energy loss of those particles is related to the excitation of vibrations (1,2). Isotope-specific vibration spectra of individual molecules have been measured with a combination of scanning tunneling microscopy (STM) and inelastic electron tunneling spectroscopy (IETS), pioneered by Stipe et al (3), where the excitation of a vibration appears as a peak in the second derivative of the current-voltage curve (4)(5)(6). STM-IETS also enables us to measure the vibrational state of a single molecule interacting with a nearby atom or molecule, e.g., the catalytic reaction between a CO molecule and O atoms on a silver surface can be controlled by changing their distance and tracked by STM-IETS (7).…”
mentioning
confidence: 99%
“…By studying these subtle changes of the vibrational energy using STM-IETS with a molecularfunctionalized tip, it has been demonstrated that STM-IETS can provide information on the inner structure of a molecule [4,5] similarly to atomic force microscopy (AFM) [6]. These advantages of STM-IETS have accelerated research in related fields [7][8][9][10][11][12][13][14][15][16]. Owing to recent progress in the theoretical description of IETS [17][18][19][20][21][22], the qualitative understanding has been improved considerably: the symmetry of the wave functions of a tip and a molecule on a substrate and a vibrational mode of the molecule are predicted to influence the efficiency of the inelastic process (γ inel ) for the tunneling current involving the molecule.…”
mentioning
confidence: 99%
“…Molecular vibrations are directly related to the molecule geometry and inter/intramolecular bonds. Hence, vibrational spectroscopy methods, such as inelastic electron tunneling, infrared, and Raman, have been widely employed to investigate the conduction mechanism and the stability of molecular devices [11][12][13][14][15][16][17][18][19]. There is also some experimental evidence that the current can modify the vibrational modes of the molecule in a junction [17][18][19].…”
Section: Introductionmentioning
confidence: 99%